Multiscore, a gene ranker powered by artificial intelligence and real-world clinical data, shows high sensitivity for the molecular diagnosis of Mendelian disorders in nearly 10,000 exomes and genomes - Vincent D. Ustach; Maria J. Guillen Sacoto; Stephen McGee; Vladimir G. Gainullin; Kevin Arvai; Amber Begtrup; Flavia M. Facio; Matthew Greenberg; Hákon Guðbjartsson; Kirsty McWalter; Francisca Millán; Kristin Monaghan; et al. (Human Genetics, 2026)

High within-herd prevalence and assessment of production impacts of Coxiella burnetii in postpartum cattle from a Scottish dairy herd - Griffin M. Weller; Ciara McKay; Maria Carvalho; Davide Pagnossin; Ryan W. Carter; Paul C.D. Johnson; Richard Vazquez Belandria; Lorenzo Viora; Kathryn J. Allan; Jo E.B. Halliday (Preventive Veterinary Medicine, 2026)

CHEF-ED: Development and Study Design of a Food Access, Healthy Cooking, and Positive Food Parenting Intervention for Parents of 3–5 Year Old Children - Margaret Raber; Sarah Goldman; Arely Balderas; Maria Papaioannou; Nilda Correa; Maria Vazquez; YaeBin Kim; Tom Power; Kathy Johnson; Christiana Beckie; Sheryl O. Hughes (Journal of Nutrition Education and Behavior, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A high-resolution record of early rift development and tectonic, sedimentary and environmental conditions in an active rift basin: IODP MSP drilling in the Corinth Rift, Greece (Expedition 381) - Lisa C. McNeill; Donna J. Shillington; Jeanine Ash; Gareth D.O. Carter; Richard E.Ll. Collier; Aleksandra Cvetkoska; Paula Diz; Mai-Linh Doan; Jeremy D. Everest; Natacha Fabregas; Eugenia Fatourou; Mary Ford; et al. (Marine Geology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Low-dose Intestinal Exposure to Botulinum Neurotoxins Increases Susceptibility to Salmonella and Shigella Infection - Federico Fabris; Paola Brun; Aram Megighian; Giulia Bernabè; Ignazio Castagliuolo; Ilenia Drigo; Luca Bano; Florigio Lista; Maria Lina Bernardini; Eric A. Johnson; Cesare Montecucco; Ornella Rossetto (Toxicon, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Strategies to build trustworthiness and increase diversity in colorectal cancer biospecimen research: a multi-phase, multi-site qualitative study - Kristi L. Roybal; Brett Nava-Coulter; Jane Roberts; Destiny Harden; Saul Castro; Anna Revette; Maria Connolly; Gina Johnson; Jennifer A. Rountree; Suzanne Brodney; Kimberly Schoolcraft; David A. Drew; et al. (Journal of Community Genetics, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

In Vitro Influence of Specific Bacteroidales Strains on Gut and Liver Health Related to Metabolic Dysfunction-Associated Fatty Liver Disease - Diego Garcia-Morena; Maria Victoria Fernandez-Cantos; Silvia Lopez Escalera; Johnson Lok; Valeria Iannone; Pierluca Cancellieri; Willem Maathuis; Gianni Panagiotou; Carmen Aranzamendi; Sahar El Aidy; Marjukka Kolehmainen; Hani El-Nezami; et al. (Probiotics and Antimicrobial Proteins, 2025)
Metabolic dysfunction-associated fatty liver disease (MAFLD) has become a major health risk and a serious worldwide issue. MAFLD typically arises from aberrant lipid metabolism, insulin resistance, oxidative stress, and inflammation. However, subjacent causes are multifactorial. The gut has been proposed as a major factor in health and disease, and over the last decade, bacterial strains with potentially beneficial effects on the host have been identified. In vitro cell models have been commonly used as an early step before in vivo drug assessment and can confer complementary advantages in gut and liver health research. In this study, several selected strains of the order Bacteroidales were used in a three-cell line in vitro analysis (HT-29, Caco-2, and HepG2 cell lines) to investigate their potential as new-generation probiotics and microbiota therapeutics. Antimicrobial activity, a potentially useful trait, was studied, and the results showed that Bacteroidales can be a source of either wide- or narrow-spectrum antimicrobials targeting other closely related strains. Moreover, Bacteroides sp. 4_1_36 induced a significant decrease in gut permeability, as evidenced by the high TEER values in the Caco-2 monolayer assay, as well as a reduction in free fatty acid accumulation and improved fatty acid clearance in a steatosis HepG2 model. These results suggest that Bacteroidales may spearhead the next generation of probiotics to prevent or diminish MAFLD.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Evaluation of blood markers of stress in beef cows during exposure to virtual fence stimuli - Juliana Ranches; Chad Boyd; Rory C. O'Connor; Matheus Ferreira; Aline Cristine Rezende dos Santos; Gracia Maria Puerto Hernandez; Dustin Johnson; David Bohnert (Rangelands, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Sperm collection in the domestic cat: A comparison of two techniques - Kristyn D. Burton; Maria C. Naskou; Douglas R. Martin; Aime K. Johnson (Theriogenology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Trends and Variability in Earth’s Energy Imbalance and Ocean Heat Uptake Since 2005 - Maria Z. Hakuba; Sébastien Fourest; Tim Boyer; Benoit Meyssignac; James A. Carton; Gaël Forget; Lijing Cheng; Donata Giglio; Gregory C. Johnson; Seiji Kato; Rachel E. Killick; Nicolas Kolodziejczyk; et al. (Surveys in Geophysics, 2024)
Earth’s energy imbalance (EEI) is a fundamental metric of global Earth system change, quantifying the cumulative impact of natural and anthropogenic radiative forcings and feedback. To date, the most precise measurements of EEI change are obtained through radiometric observations at the top of the atmosphere (TOA), while the quantification of EEI absolute magnitude is facilitated through heat inventory analysis, where ~ 90% of heat uptake manifests as an increase in ocean heat content (OHC). Various international groups provide OHC datasets derived from in situ and satellite observations, as well as from reanalyses ingesting many available observations. The WCRP formed the GEWEX-EEI Assessment Working Group to better understand discrepancies, uncertainties and reconcile current knowledge of EEI magnitude, variability and trends. Here, 21 OHC datasets and ocean heat uptake (OHU) rates are intercompared, providing OHU estimates ranging between 0.40 ± 0.12 and 0.96 ± 0.08 W m −2 (2005–2019), a spread that is slightly reduced when unequal ocean sampling is accounted for, and that is largely attributable to differing source data, mapping methods and quality control procedures. The rate of increase in OHU varies substantially between − 0.03 ± 0.13 (reanalysis product) and 1.1 ± 0.6 W m −2 dec −1 (satellite product). Products that either more regularly observe (satellites) or fill in situ data-sparse regions based on additional physical knowledge (some reanalysis and hybrid products) tend to track radiometric EEI variability better than purely in situ-based OHC products. This paper also examines zonal trends in TOA radiative fluxes and the impact of data gaps on trend estimates. The GEWEX-EEI community aims to refine their assessment studies, to forge a path toward best practices, e.g., in uncertainty quantification, and to formulate recommendations for future activities.

Litchi (Litchi chinensis Sonn.): A comprehensive and critical review on cancer prevention and intervention - Anupam Bishayee; Joachim Kavalakatt; Charvi Sunkara; Olivia Johnson; Shweta S. Zinzuwadia; Taylor E. Collignon; Sabyasachi Banerjee; Sandra Maria Barbalho (Food Chemistry, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Benefits of calorie restriction in mice are mediated via energy imbalance, not absolute energy or protein intake - Daniel L. Smith; Sharon E. Mitchell; Maria S. Johnson; Victoria K. Gibbs; Stephanie Dickinson; Beate Henschel; Rui Li; Kathryn A. Kaiser; Daniella E. Chusyd; Andrew W. Brown; David B. Allison; John R. Speakman; et al. (GeroScience, 2024)
Caloric restriction (CR) results in reduced energy and protein intake, raising questions about protein restriction’s contribution to CR longevity benefits. We kept ad libitum ( AL )–fed male C57BL/6J mice at 27°C (AL27) and pair-fed (PF) mice at 22°C (22(PF27)). The 22(PF27) group was fed to match AL27 while restricted for calories due to cold-induced metabolism. The 22(PF27) mice had significantly lower body weight, lean mass, fat mass, leptin, IGF-1, and TNF-α levels than AL27 mice ( p <0.001 for all). Manipulations over ~11 weeks resulted in significant differences in body temperature, physical activity, and expression of key genes linked to hunger in the hypothalamus. Survival was significantly greater in 22(PF27) compared to AL27 overall ( p <0.001). CR in the context of equivalent energy and protein intake resulted in hormonal, metabolic, and physiological benefits and extended longevity. Hence, energy imbalance, rather than low energy or protein intake per se, mediates the benefits of CR.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Investigating impacts of the mycothiazole chemotype as a chemical probe for the study of mitochondrial function and aging - Naibedya Dutta; Joe A. Gerke; Sofia F. Odron; Joseph D. Morris; Adam Hruby; Juri Kim; Toni Castro Torres; Sarah J. Shemtov; Jacqueline G. Clarke; Michelle C. Chang; Hooriya Shaghasi; Marissa N. Ray; et al. (GeroScience, 2024)
Small molecule inhibitors of the mitochondrial electron transport chain (ETC) hold significant promise to provide valuable insights to the field of mitochondrial research and aging biology. In this study, we investigated two molecules: mycothiazole (MTZ) - from the marine sponge C. mycofijiensis and its more stable semisynthetic analog 8- O -acetylmycothiazole (8-OAc) as potent and selective chemical probes based on their high efficiency to inhibit ETC complex I function. Similar to rotenone (Rote), MTZ, a newly employed ETC complex I inhibitor, exhibited higher cytotoxicity against cancer cell lines compared to certain non-cancer cell lines. Interestingly, 8-OAc demonstrated greater selectivity for cancer cells when compared to both MTZ and Rote, which has promising potential for anticancer therapeutic development. Furthermore, in vivo experiments with these small molecules utilizing a C. elegans model demonstrate their unexplored potential to investigate aging studies. We observed that both molecules have the ability to induce a mitochondria-specific unfolded protein response (UPR MT ) pathway, that extends lifespan of worms when applied in their adult stage. We also found that these two molecules employ different pathways to extend lifespan in worms. Whereas MTZ utilizes the transcription factors ATFS-1 and HSF1, which are involved in the UPR MT and heat shock response (HSR) pathways respectively, 8-OAc only required HSF1 and not ATFS-1 to mediate its effects. This observation underscores the value of applying stable, potent, and selective next generation chemical probes to elucidate an important insight into the functional roles of various protein subunits of ETC complexes and their regulatory mechanisms associated with aging. Graphical Abstract

Reproductive factors, hormonal interventions, and gastric cancer risk in the Stomach cancer Pooling (StoP) Project - Minkyo Song; Harindra Jayasekara; Claudio Pelucchi; Charles S. Rabkin; Kenneth C. Johnson; Jinfu Hu; Domenico Palli; Monica Ferraroni; Linda M. Liao; Rossella Bonzi; David Zaridze; Dmitry Maximovitch; et al. (Cancer Causes & Control, 2024)

Capacity gaps in land-based mitigation technologies and practices: A first stock take - Stefan Bößner; Maria Xylia; Bibiana Bilbao; Siti N. Indriani; Moritz Laub; Eric Rahn; Luis D. Virla; Francis X. Johnson (Land Use Policy, 2023)

The importance of the seafood processing sector to coastal community resilience - Lori A. Cramer; Jennifer Beaullieu; Jamie Doyle; Marta Maldonado; Hillary Egna; Maria Johnson; Flaxen D.L. Conway (Marine Policy, 2023)

Towards a better future for biodiversity and people: Modelling Nature Futures - HyeJin Kim; Garry D. Peterson; William W.L. Cheung; Simon Ferrier; Rob Alkemade; Almut Arneth; Jan J. Kuiper; Sana Okayasu; Laura Pereira; Lilibeth A. Acosta; Rebecca Chaplin-Kramer; Eefje den Belder; et al. (Global Environmental Change, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

The living infinite: Envisioning futures for transformed human-nature relationships on the high seas - Laura M. Pereira; Guillermo Ortuño Crespo; Diva J. Amon; Renuka Badhe; Salomão Bandeira; Frida Bengtsson; Miranda Boettcher; Gabrielle Carmine; William W.L. Cheung; Bwalya Chibwe; Daniel Dunn; Maria A. Gasalla; et al. (Marine Policy, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Long-term trends in crayfish invasions across European rivers - Ismael Soto; Danish A. Ahmed; Ayah Beidas; Francisco J. Oficialdegui; Elena Tricarico; David G. Angeler; Giuseppe Amatulli; Elizabeta Briski; Thibault Datry; Alain Dohet; Sami Domisch; Judy England; et al. (Science of The Total Environment, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

DoPI: The Database of Pollinator Interactions - Nicholas J. Balfour; Maria Clara Castellanos; Dave Goulson; Andrew Philippides; Chris Johnson (Ecology, 2022)
Despite the importance of pollinating insects to natural environments and agriculture, there have been few attempts to unite the existing plant–pollinator interaction datasets into a single depository using a common format. Accordingly, we have created one of the world's first online, open‐access, and searchable pollinator–plant interaction databases. DoPI (The Database of Pollinator Interactions) was built from a systematic review of the scientific literature and unpublished datasets requested from researchers and organizations. We collated records of interactions between British plant and insect flower–visitor species (or genera), together with associated metadata (date, location, habitat, source publication) when available. The dataset currently (December 2021) contains 101,539 records, detailing over 320,000 interactions. The number of interactions (i.e., the number of times a pairwise species interaction was recorded per occasion) varies considerably among records, averaging 3.6. These include records from 1888 pollinator species and 1241 plant species, totaling >17,000 pairwise species interactions. By combining a large volume of information in a single repository, DoPI can be used to answer fundamental ecological questions on the dynamics of pollination interactions in space and time, as well as applied questions in conservation practice. We hope this dynamic database will be a useful tool not only for researchers, but also for conservationists, funding agencies, governmental departments, beekeepers, agronomists, and gardeners. We request that this paper is cited when using the data in publications and individual studies when appropriate. Researchers and organizations are encouraged to add further data in the future. The database can be accessed at: https://www.dopi.org.uk/ .

Effects of meteorological and land surface modeling uncertainty on errors in winegrape ET calculated with SIMS - Conor T. Doherty; Lee F. Johnson; John Volk; Meagan S. Mauter; Nicolas Bambach; Andrew J. McElrone; Joseph G. Alfieri; Lawrence E. Hipps; John H. Prueger; Sebastian J. Castro; Maria Mar Alsina; William P. Kustas; et al. (Irrigation Science, 2022)
Characterization of model errors is important when applying satellite-driven evapotranspiration (ET) models to water resource management problems. This study examines how uncertainty in meteorological forcing data and land surface modeling propagate through to errors in final ET data calculated using the Satellite Irrigation Management Support (SIMS) model, a computationally efficient ET model driven with satellite surface reflectance values. The model is applied to three instrumented winegrape vineyards over the 2017–2020 time period and the spatial and temporal variation in errors are analyzed. We illustrate how meteorological data inputs can introduce biases that vary in space and at seasonal timescales, but that can persist from year to year. We also observe that errors in SIMS estimates of land surface conductance can have a particularly strong dependence on time of year. Overall, meteorological inputs introduced RMSE of 0.33–0.65 mm/day (7–27%) across sites, while SIMS introduced RMSE of 0.55–0.83 mm/day (19–24%). The relative error contribution from meteorological inputs versus SIMS varied across sites; errors from SIMS were larger at one site, errors from meteorological inputs were larger at a second site, and the error contributions were of equal magnitude at the third site. The similar magnitude of error contributions is significant given that many satellite-driven ET models differ in their approaches to estimating land surface conductance, but often rely on similar or identical meteorological forcing data. The finding is particularly notable given that SIMS makes assumptions about the land surface (no soil evaporation or plant water stress) that do not always hold in practice. The results of this study show that improving SIMS by eliminating these assumptions would result in meteorological inputs dominating the error budget of the model on the whole. This finding underscores the need for further work on characterizing spatial uncertainty in the meteorological forcing of ET.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Invasion impacts and dynamics of a European‐wide introduced species - Phillip J. Haubrock; Danish A. Ahmed; Ross N. Cuthbert; Rachel Stubbington; Sami Domisch; Jaime R. G. Marquez; Ayah Beidas; Giuseppe Amatulli; Jens Kiesel; Longzhu Q. Shen; Ismael Soto; David G. Angeler; et al. (Global Change Biology, 2022)
Globalization has led to the introduction of thousands of alien species worldwide. With growing impacts by invasive species, understanding the invasion process remains critical for predicting adverse effects and informing efficient management. Theoretically, invasion dynamics have been assumed to follow an “invasion curve” (S‐shaped curve of available area invaded over time), but this dynamic has lacked empirical testing using large‐scale data and neglects to consider invader abundances. We propose an “impact curve” describing the impacts generated by invasive species over time based on cumulative abundances. To test this curve's large‐scale applicability, we used the data‐rich New Zealand mud snail Potamopyrgus antipodarum , one of the most damaging freshwater invaders that has invaded almost all of Europe. Using long‐term (1979–2020) abundance and environmental data collected across 306 European sites, we observed that P. antipodarum abundance generally increased through time, with slower population growth at higher latitudes and with lower runoff depth. Fifty‐nine percent of these populations followed the impact curve, characterized by first occurrence, exponential growth, then long‐term saturation. This behaviour is consistent with boom‐bust dynamics, as saturation occurs due to a rapid decline in abundance over time. Across sites, we estimated that impact peaked approximately two decades after first detection, but the rate of progression along the invasion process was influenced by local abiotic conditions. The S‐shaped impact curve may be common among many invasive species that undergo complex invasion dynamics. This provides a potentially unifying approach to advance understanding of large‐scale invasion dynamics and could inform timely management actions to mitigate impacts on ecosystems and economies.

The Need for a Global Ocean Vision Within Biodiversity Beyond National Jurisdiction: A Key Role for Strategic Environmental Assessment - Maria Adelaide Ferreira; David E. Johnson; Francisco Andrade (Frontiers in Marine Science, 2022)
An ecosystem-based forward-looking vision for the global ocean, encompassing ocean health and productivity, ecosystem integrity and resilience, incorporating area beyond national jurisdiction, is fundamental. A vision which is holistic and universally acceptable to guide future sustainable ocean policies, plans and programmes (PPPs). We argue that Strategic Environmental Assessment (SEA) is the best available framework to develop such a vision and its suitability for this purpose should be recognised within the on-going process to negotiate an International Legally Binding Instrument (ILBI) for the conservation and sustainable use of Biodiversity Beyond National Jurisdiction (BBNJ Agreement). This perspective paper justifies why such an ecosystem-based Global Ocean Vision is essential. It then describes the key characteristics it must integrate and how it can be elaborated in the framework of a collective SEA within the BBNJ process. We advocate expanding text in Part I General Provisions of the draft BBNJ Agreement to include development of such a global ocean vision. We conclude by highlighting the opportunity and timeliness of this proposal, with the fifth session of the IGC of BBNJ tentatively scheduled for August 2022.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Pathway-Centric Analysis of Microbial Metabolic Potential and Expression Along Nutrient and Energy Gradients in the Western Atlantic Ocean - Maria A. Cavaco; Maya P. Bhatia; Alyse K. Hawley; Monica Torres-Beltrán; Winifred M. Johnson; Krista Longnecker; Kishori Konwar; Elizabeth B. Kujawinski; Steven J. Hallam (Frontiers in Marine Science, 2022)
Microbial communities play integral roles in driving nutrient and energy transformations in the ocean, collectively contributing to fundamental biogeochemical cycles. Although it is well known that these communities are stratified within the water column, there remains limited knowledge of how metabolic pathways are distributed and expressed. Here, we investigate pathway distribution and expression patterns from surface (5 m) to deep dark ocean (4000 m) at three stations along a 2765 km transect in the western South Atlantic Ocean. This study is based on new data, consisting of 43 samples for 16S rRNA gene sequencing, 20 samples for metagenomics and 19 samples for metatranscriptomics. Consistent with previous observations, we observed vertical zonation of microbial community structure largely partitioned between light and dark ocean waters. The metabolic pathways inferred from genomic sequence information and gene expression stratified with depth. For example, expression of photosynthetic pathways increased in sunlit waters. Conversely, expression of pathways related to carbon conversion processes, particularly those involving recalcitrant and organic carbon degradation pathways (i.e., oxidation of formaldehyde) increased in dark ocean waters. We also observed correlations between indicator taxa for specific depths with the selective expression of metabolic pathways. For example, SAR202, prevalent in deep waters, was strongly correlated with expression of the methanol oxidation pathway. From a biogeographic perspective, microbial communities along the transect encoded similar metabolic potential with some latitudinal stratification in gene expression. For example, at a station influenced by input from the Amazon River, expression of pathways related to oxidative stress was increased. Finally, when pairing distinct correlations between specific particulate metabolites (e.g., DMSP, AMP and MTA) and both the taxonomic microbial community and metatranscriptomic pathways across depth and space, we were able to observe how changes in the marine metabolite pool may be influenced by microbial function and vice versa. Taken together, these results indicate that marine microbial communities encode a core repertoire of widely distributed metabolic pathways that are differentially regulated along nutrient and energy gradients. Such pathway distribution patterns are consistent with robustness in microbial food webs and indicate a high degree of functional redundancy.

Conventional versus drug-eluting embolic transarterial chemoembolization with doxorubicin: comparative drug delivery, pharmacokinetics, and treatment response in a rabbit VX2 tumor model - Ron C. Gaba; Ramzy C. Khabbaz; Ruth N. Muchiri; Joseph D. Morrison; Lobna Elkhadragy; William M. Totura; Jonathan P. Samuelson; Herbert E. Whiteley; Ryan L. Deaton; Peter L. Nguyen; Maria Sverdlov; Jeremy J. Johnson; et al. (Drug Delivery and Translational Research, 2022)

Salt intake and gastric cancer: a pooled analysis within the Stomach cancer Pooling (StoP) Project - Samantha Morais; Adriana Costa; Gabriela Albuquerque; Natália Araújo; Claudio Pelucchi; Charles S. Rabkin; Linda M. Liao; Rashmi Sinha; Zuo-Feng Zhang; Jinfu Hu; Kenneth C. Johnson; Domenico Palli; et al. (Cancer Causes & Control, 2022)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

A National Status Report on United States Coral Reefs Based on 2012–2018 Data From National Oceanic and Atmospheric Administration’s National Coral Reef Monitoring Program - Erica K. Towle; E. Caroline Donovan; Heath Kelsey; Mary E. Allen; Hannah Barkley; Jeremiah Blondeau; Russell E. Brainard; Annie Carew; Courtney S. Couch; Maria K. Dillard; C. Mark Eakin; Kimberly Edwards; et al. (Frontiers in Marine Science, 2022)
National Oceanic and Atmospheric Administration’s Coral Reef Conservation Program supports the National Coral Reef Monitoring Program (NCRMP) in the United States Pacific, Atlantic, Caribbean, and Gulf of Mexico. NCRMP conducts standardized observations of biological, climatic, and socioeconomic indicators across American Samoa, Guam, the Main Hawaiian Islands, the Northwestern Hawaiian Islands, the Northern Mariana Islands, the Pacific Remote Islands, Florida, the Flower Garden Banks, Puerto Rico, and the United States Virgin Islands. NCRMP provides periodic, national-level assessments of the status of United States coral reef ecosystems and communities connected to them. In 2014, NCRMP partnered with the University of Maryland Center for Environmental Science on an unprecedented collaboration between federal and jurisdictional/state agencies, academia, and non-governmental organizations to synthesize NCRMP data into a reporting format designed to be accessible and relevant to the public and policy makers. The process involved multi-year data analyses of key benthic, fish, and climate indicators. In populated jurisdictions, socioeconomic data were integrated to assess public support for management actions, participation in pro-environmental behaviors, and awareness of threats to coral reefs. Jurisdictions were scored using a report-card scale (0–100%) by establishing references for each indicator using best-available historical data or expert opinion where historical data did not exist or were not statistically comparable. Despite overall ecosystem scores of Fair for all combined Atlantic (70%) and Pacific (74%) jurisdictions, the current trend is downward with a majority of United States coral reefs declining and vulnerable to further degradation. Remote, uninhabited reefs had an advantage with respect to reef fish population scores, i.e., Flower Garden Banks (85%) and Pacific Remote Islands (93%), when compared to populated location scores, i.e., Puerto Rico (63%) and Main Hawaiian Islands (66%). All coral reefs are highly impacted by climate change, and climate impacts were more pronounced than expected on remote reefs, i.e., the Northwestern Hawaiian Islands (58%). Presenting results in a report-card style facilitates communication to the public and policy makers, and provides a useful mechanism to garner support for management actions such as expanding protected areas; enforcing existing regulations; increasing climate change education; reducing land-based sources of pollution; and other actions to improve the trajectory of coral reef ecosystem conditions.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)

Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)
Microscale thermophoresis (MST), and the closely related Temperature Related Intensity Change (TRIC), are synonyms for a recently developed measurement technique in the field of biophysics to quantify biomolecular interactions, using the (capillary-based) NanoTemper Monolith and (multiwell plate-based) Dianthus instruments. Although this technique has been extensively used within the scientific community due to its low sample consumption, ease of use, and ubiquitous applicability, MST/TRIC has not enjoyed the unambiguous acceptance from biophysicists afforded to other biophysical techniques like isothermal titration calorimetry (ITC) or surface plasmon resonance (SPR). This might be attributed to several facts, e.g., that various (not fully understood) effects are contributing to the signal, that the technique is licensed to only a single instrument developer, NanoTemper Technology, and that its reliability and reproducibility have never been tested independently and systematically. Thus, a working group of ARBRE-MOBIEU has set up a benchmark study on MST/TRIC to assess this technique as a method to characterize biomolecular interactions. Here we present the results of this study involving 32 scientific groups within Europe and two groups from the US, carrying out experiments on 40 Monolith instruments , employing a standard operation procedure and centrally prepared samples. A protein–small molecule interaction, a newly developed protein–protein interaction system and a pure dye were used as test systems. We characterized the instrument properties and evaluated instrument performance, reproducibility, the effect of different analysis tools, the influence of the experimenter during data analysis, and thus the overall reliability of this method.

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

The lateral hypothalamus and orexinergic transmission in the paraventricular thalamus promote the attribution of incentive salience to reward-associated cues - Joshua L. Haight; Paolo Campus; Cristina E Maria-Rios; Allison M. Johnson; Marin S. Klumpner; Brittany N. Kuhn; Ignacio R. Covelo; Jonathan D. Morrow; Shelly B. Flagel (Psychopharmacology, 2020)

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Lumbar spinal cord microglia exhibited increased activation in aging dogs compared with young adult dogs - Christine M. Toedebusch; Virginia B. Garcia; John C. Snyder; Maria R. Jones; David J Schulz; Gayle C. Johnson; Eric Villalón; Joan R. Coates; Michael L. Garcia (GeroScience, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Towards a macroscope: Leveraging technology to transform the breadth, scale and resolution of macroecological data - Maria Dornelas; Elizabeth M. P. Madin; Michael Bunce; Joseph D. DiBattista; Mark Johnson; Joshua S. Madin; Anne E. Magurran; Brian J. McGill; Nathalie Pettorelli; Oscar Pizarro; Stefan B. Williams; Marten Winter; et al. (Global Ecology and Biogeography, 2019)
The problem Earth‐based observations of the biosphere are spatially biased in ways that can limit our ability to detect macroecological patterns and changes in biodiversity. To resolve this problem, we need to supplement the ad hoc data currently collected with planned biodiversity monitoring, in order to approximate global stratified random sampling of the planet. We call this all‐encompassing observational system ‘the macroscope’. The solution With a focus on the marine realm, we identify seven main biosphere observation tools that compose the macroscope: satellites, drones, camera traps, passive acoustic samplers, biologgers, environmental DNA and human observations. By deploying a nested array of these tools that fills current gaps in monitoring, we can achieve a macroscope fit for purpose and turn these existing powerful tools into more than the sum of their parts. An appeal Building a macroscope requires commitment from many fields, together with coordinated actions to attract the level of funding required for such a venture. We call on macroecologists to become advocates for the macroscope and to engage with existing global observation networks.

Corrigendum: A Response to Scientific and Societal Needs for Marine Biological Observations - Nicholas J. Bax; Patricia Miloslavich; Frank Edgar Muller-Karger; Valerie Allain; Ward Appeltans; Sonia Dawn Batten; Lisandro Benedetti-Cecchi; Pier Luigi Buttigieg; Sanae Chiba; Daniel Paul Costa; J. Emmett Duffy; Daniel C. Dunn; et al. (Frontiers in Marine Science, 2019)

Correction to: Wheat wounding-responsive HD-Zip IV transcription factor GL7 is predominantly expressed in grain and activates genes encoding defensins - Nataliya Kovalchuk; Wei Wu; Natalia Bazanova; Nicolas Reid; Rohan Singh; Neil Shirley; Omid Eini; Alexander A. T. Johnson; Peter Langridge; Maria Hrmova; Sergiy Lopato (Plant Molecular Biology, 2019)

Wheat wounding-responsive HD-Zip IV transcription factor GL7 is predominantly expressed in grain and activates genes encoding defensins - Nataliya Kovalchuk; Wei Wu; Natalia Bazanova; Nicolas Reid; Rohan Singh; Neil Shirley; Omid Eini; Alexander A. T. Johnson; Peter Langridge; Maria Hrmova; Sergiy Lopato (Plant Molecular Biology, 2019)

Measuring Global Ocean Heat Content to Estimate the Earth Energy Imbalance - Benoit Meyssignac; Tim Boyer; Zhongxiang Zhao; Maria Z. Hakuba; Felix W. Landerer; Detlef Stammer; Armin Köhl; Seiji Kato; Tristan L’Ecuyer; Michael Ablain; John Patrick Abraham; Alejandro Blazquez; et al. (Frontiers in Marine Science, 2019)

A Response to Scientific and Societal Needs for Marine Biological Observations - Nicholas J. Bax; Patricia Miloslavich; Frank Edgar Muller-Karger; Valerie Allain; Ward Appeltans; Sonia Dawn Batten; Lisandro Benedetti-Cecchi; Pier Luigi Buttigieg; Sanae Chiba; Daniel Paul Costa; J. Emmett Duffy; Daniel C. Dunn; et al. (Frontiers in Marine Science, 2019)

A feasibility study comparing objective and subjective field-based physical exposure measurements during apple harvesting with ladders and mobile platforms - Ornwipa Thamsuwan; Kit Galvin; Maria Tchong-French; Jeong Ho Kim; Peter W. Johnson (Journal of Agromedicine, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Echoes of the whispering land: interacting roles of vicariance and selection in shaping the evolutionary divergence of two Calceolaria (Calceolariaceae) species from Patagonia and Malvinas/Falkland Islands - Matías Cristian Baranzelli; Andrea Cosacov; Anahí Espíndola; Maria del Rosario Iglesias; Lauren M. Chan; Leigh A. Johnson; Alicia Noemí Sérsic (Evolutionary Ecology, 2018)

Response to “Resilience of harbor porpoises to anthropogenic disturbance: Must they really feed continuously?” - Danuta Maria Wisniewska; Mark Johnson; Jonas Teilmann; Laia Rojano‐Doñate; Jeanne Shearer; Signe Sveegaard; Lee A. Miller; Ursula Siebert; Peter Teglberg Madsen (Marine Mammal Science, 2018)

Ocean acidification alters zooplankton communities and increases top‐down pressure of a cubozoan predator - Edd Hammill; Ellery Johnson; Trisha B. Atwood; Januar Harianto; Charles Hinchliffe; Piero Calosi; Maria Byrne (Global Change Biology, 2018)
The composition of local ecological communities is determined by the members of the regional community that are able to survive the abiotic and biotic conditions of a local ecosystem. Anthropogenic activities since the industrial revolution have increased atmospheric CO 2 concentrations, which have in turn decreased ocean pH and altered carbonate ion concentrations: so called ocean acidification (OA). Single‐species experiments have shown how OA can dramatically affect zooplankton development, physiology and skeletal mineralization status, potentially reducing their defensive function and altering their predatory and antipredatory behaviors. This means that increased OA may indirectly alter the biotic conditions by modifying trophic interactions. We investigated how OA affects the impact of a cubozoan predator on their zooplankton prey, predominantly Copepoda, Pleocyemata, Dendrobranchiata, and Amphipoda. Experimental conditions were set at either current ( p CO 2 370 μatm) or end‐of‐the‐century OA ( p CO 2 1,100 μatm) scenarios, crossed in an orthogonal experimental design with the presence/absence of the cubozoan predator Carybdea rastoni . The combined effects of exposure to OA and predation by C. rastoni caused greater shifts in community structure, and greater reductions in the abundance of key taxa than would be predicted from combining the effect of each stressor in isolation. Specifically, we show that in the combined presence of OA and a cubozoan predator, populations of the most abundant member of the zooplankton community (calanoid copepods) were reduced 27% more than it would be predicted based on the effects of these stressors in isolation, suggesting that OA increases the susceptibility of plankton to predation. Our results indicate that the ecological consequences of OA may be greater than predicted from single‐species experiments, and highlight the need to understand future marine global change from a community perspective.

Facilitators of Survivorship Care Among Underserved Breast Cancer Survivors: a Qualitative Study - Amy E. Ustjanauskas; Gwendolyn P. Quinn; Tonya M. Pan; Maria Rivera; Coralia Vázquez-Otero; Danielle Ung; Richard G. Roetzheim; Christine Laronga; Kenneth Johnson; Marilyn Norton; Claudia Carrizosa; Dariana Muñoz; et al. (Journal of Cancer Education, 2017)

Mother–infant interactions and regional brain volumes in infancy: an MRI study - Vaheshta Sethna; Inês Pote; Siying Wang; Maria Gudbrandsen; Anna Blasi; Caroline McCusker; Eileen Daly; Emily Perry; Kerrie P. H. Adams; Maria Kuklisova-Murgasova; Paula Busuulwa; Sarah Lloyd-Fox; et al. (Brain Structure and Function, 2017)

The role of functional uniqueness and spatial aggregation in explaining rarity in trees - María Natalia Umaña; Xiangcheng Mi; Min Cao; Brian J. Enquist; Zhanqing Hao; Robert Howe; Yoshiko Iida; Daniel Johnson; Luxiang Lin; Xiaojuan Liu; Keping Ma; I‐Fang Sun; et al. (Global Ecology and Biogeography, 2017)
Aim Determining the drivers of species rarity is fundamental for understanding and conserving biodiversity. Rarity of a given species within its community may arise due to exclusion by other ecologically similar species. Conversely, rare species may occupy habitats that are rare in the landscape or they may be ill‐suited to all available habitats. The first mechanism would lead to common and rare species occupying similar ecological space defined by functional traits. The second mechanism would result in common and rare species occupying dissimilar ecological space and spatial aggregation of rare species, either because they are specialists in rare habitats or because rare species tend to be dispersal limited. Here, we quantified the contribution of locally rare species to community functional richness and the spatial aggregation of species across tree communities world‐wide to address these hypotheses. Location Asia and the Americas. Time period 2002 to 2012 (period that considers the censuses for the plots used). Major taxa studied Angiosperm and Gymnosperm trees. Methods We compiled a dataset of functional traits from all the species present in eight tree plots around the world to evaluate the contribution of locally rare species to tree community functional richness using multi‐ and univariate approaches. We also quantified the spatial aggregation of individuals within species at several spatial scales as it relates to abundance. Results Locally rare tree species in temperate and tropical forests tended to be functionally unique and are consistently spatially clustered. Furthermore, there is no evidence that this pattern is driven by pioneer species being locally rare. Main conclusions This evidence shows that locally rare tree species disproportionately contribute to community functional richness, and we can therefore reject the hypothesis that locally rare species are suppressed by ecologically similar, but numerically dominant, species. Rather, locally rare species are likely to be specialists on spatially rare habitats or they may be ill‐suited to the locally available environments.

QTL and major genes influencing grain yield potential in soft red winter wheat adapted to the southern United States - Christopher K. Addison; R. Esten Mason; Gina Brown-Guedira; Mohammed Guedira; Yuanfeng Hao; Randall G. Miller; Nithya Subramanian; Dennis N. Lozada; Andrea Acuna; Maria N. Arguello; Jerry W. Johnson; Amir M. H. Ibrahim; et al. (Euphytica, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Clonal Immortalized Human Glial Cell Lines Support Varying Levels of JC Virus Infection due to Differences in Cellular Gene Expression - Michael W. Ferenczy; Kory R. Johnson; Shannon M. Steinberg; Leslie J. Marshall; Maria Chiara Monaco; Alexander M. Beschloss; Peter N. Jensen; Eugene O. Major (Journal of Neuroimmune Pharmacology, 2013)

VACM-1/cul5 expression in vascular tissue in vivo is induced by water deprivation and its expression in vitro regulates aquaporin-1 concentrations - Alyssa E. Johnson; Isabelle P. Le; Bradley T. Andresen; Joseph Stodola; Gary L. Dewey; Shirley B. Dean; James Resau; Pete Haak; Travis Ruch; Ashleigh Sartor; Inara Lazdins; Christopher C. Barney; et al. (Cell and Tissue Research, 2012)

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Microsatellite analysis supports mitochondrial phylogeography of the hellbender (Cryptobranchus alleganiensis) - Maria Tonione; Jarrett R. Johnson; Eric J. Routman (Genetica, 2011)

Meeting Report: Applied Biopharmaceutics and Quality by Design for Dissolution/Release Specification Setting: Product Quality for Patient Benefit - Arzu Selen; Maria T. Cruañes; Anette Müllertz; Paul A. Dickinson; Jack A. Cook; James E. Polli; Filippos Kesisoglou; John Crison; Kevin C. Johnson; Gordon T. Muirhead; Timothy Schofield; Yi Tsong (The AAPS Journal, 2010)

An Overview of Global Observing Systems Relevant to GODAE - Candyce Clark; D.E. Harrison; Mike Johnson; Graeme Ball; Howard Freeland; Gustavo Goni; Maria Hood; Michael McPhaden; David Meldrum; Mark Merrifield; Dean Roemmich; Chris Sabine; et al. (Oceanography, 2009)

Epigenetic regulation of cardiac muscle-specific genes in H9c2 cells by Interleukin-18 and histone deacetylase inhibitor m-carboxycinnamic acid bis-hydroxamide - Gipsy Majumdar; I. Maria Johnson; Santosh Kale; Rajendra Raghow (Molecular and Cellular Biochemistry, 2008)

Single cell adhesion measuring apparatus (SCAMA): application to cancer cell lines of different metastatic potential and voltage-gated Na+ channel expression - Christopher P. Palmer; Maria E. Mycielska; Hakan Burcu; Kareem Osman; Timothy Collins; Rachel Beckerman; Rebecca Perrett; Helen Johnson; Ebru Aydar; Mustafa B. A. Djamgoz (European Biophysics Journal, 2008)

A Comparison of 18Oδ Composition of Water Extracted from Suction Lysimeters, Centrifugation, and Azeotropic Distillation - Maria A. Figueroa-Johnson; James A. Tindall; Michael Friedel (Water, Air, & Soil Pollution, 2007)

Estrogen-dependent growth and estrogen receptor (ER)-α concentration in T47D breast cancer cells are inhibited by VACM-1, a cul 5 gene - Alyssa E. Johnson; Isabelle P. Le; Abby Buchwalter; Maria A. Burnatowska-Hledin (Molecular and Cellular Biochemistry, 2007)

Downstream and Coastal Impacts of Damming and Water Abstraction in Africa - Maria Snoussi; Johnson Kitheka; Yohanna Shaghude; Alioune Kane; Russell Arthurton; Martin Le Tissier; Hassan Virji (Environmental Management, 2007)

Clinical and molecular genetic features of ARC syndrome - Paul Gissen; Louise Tee; Colin A. Johnson; Emmanuelle Genin; Almuth Caliebe; David Chitayat; Carol Clericuzio; Jonas Denecke; Maja Di Rocco; Björn Fischler; David FitzPatrick; Angeles García-Cazorla; et al. (Human Genetics, 2006)

Modulation of DNA intercalation by resveratrol and genistein - Subbiah Usha; Irudayam Maria Johnson; Raghunathan Malathi (Molecular and Cellular Biochemistry, 2006)

Serotonin transport kinetics correlated between human platelets and brain synaptosomes - Jeffrey L. Rausch; Maria E. Johnson; Junqing Li; Julian Hutcheson; Benjamin M. Carr; Katina M. Corley; Amanda B. Gowans; Joseph Smith (Psychopharmacology, 2005)

EFFECTS OF ETHANOL AND HYDROGEN PEROXIDE ON MOUSE LIMB BUD MESENCHYME DIFFERENTIATION AND CELL DEATH - COREY S. JOHNSON; MARIA R. BLANTON; E. SIDNEY HUNTER (In Vitro Cellular & Developmental Biology - Animal, 2004)

EXPLANT-CELL CULTURE OF PRIMARY MAMMARY TUMORS FROM MMTV-c-Myc TRANSGENIC MICE - XU FANG PEI; MARCIA S. NOBLE; MARIA ANTONIETTA DAVOLI; EDWARD ROSFJORD; MADDALENA T. TILLI; PRISCILLA A. FURTH; ROBERT RUSSELL; MICHAEL D. JOHNSON; ROBERT B. DICKSON (In Vitro Cellular & Developmental Biology - Animal, 2004)

Effects of ethanol and hydrogen peroxide on mouse limb bud mesenchyme differentiation and cell death - Corey Johnson; Maria Blanton; E. Hunter (In Vitro Cellular & Developmental Biology - Animal, 2004)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Testicular atrophy and loss of nerve growth factor-immunoreactive germ cell line in rats exposed to n-hexane and a protective effect of simultaneous exposure to toluene or xylene - Per Nyln; Ted Ebendal; Maria Eriksdotter-Nilsson; Tiiu Hansson; Andreas Henschen; Ann-Christin Johnson; Tony Kronevi; Ulrik Kvist; Nils O. Sjstrand; Gunnar Hglund; Lars Olson (Archives of Toxicology, 1989)